Performance-Based Assessment: Techniques for Resourceful Teaching, a comprehensible plan how students can to dominant the skills - Khan, Aayesha Sagir; Khan, Sagir Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
Assessment plays a vital role in a student’s life. The complete motivation cycle is based on it. Performance-based assessment is a teaching technique that permits the student to create his or her own answers or response as compared to simply selecting from a list provided in the question paper to evaluate the knowledge of the student. Both student and teacher are made aware in advance of the skills and knowledge to be learned, as well as the criteria for judging performance. The research done in this paper on 100 students of King Khalid University, and it makes an attempt to present an overview of what performance-based assessment is, role of teacher, student motivation which is one of the most important aspect and likewise disadvantage of the technique for the university students. The main purpose is to involve this technique for assessments and to determine a student’s strengths in a particular skill which will further help him in the global business world.